Social Media-Based E-learning and Online Assignments on Algebraic Materials - Miftah Sigit Rahmawati; Rendra Soekarta (Jurnal Pendidikan Matematika, 2021)
This study aims at evaluating the application of social media-based e-learning and online assignments during Covid-19 pandemic based on: (1) the availability of facilities and infrastructure in implementing social media-based e-learning and online assignments during the Covid-19 pandemic, (2) comprehension and management of e-learning and online assignments by lecturers and students, (3) social media-based e-learning and online assignments. This study is a qualitative descriptive study using the CIPP evaluation by evaluating each component, including context, input, process and product/outcome. The sources of study data involved lecturers and students of Informatics Engineering at Muhammadiyah University Sorong in Matrix Algebra course. The instruments of primary data collection was online assignments and Google Form questionnaires, while secondary data was obtained through observation, literature study, documentation and interviews. The results show that students obtained an overall average score (mean) of 76.4 from the maximum score of 100, and a percentage of assignment collection of 65.78%. This results were categorized as adequate, in meaning it is rather effective for theory comprehension, and was categorized as moderate in terms of boosting students’ motivation in doing social media-based online assignments, depending on the type of assignment. This signifies that the evaluation of CIPP in social media-based e-learning and online assignments in algebra has positive outcome in terms of infrastructure, management, and use.